DIDACTIC GAME LESSONS - Boqiyeva Marjona Shuhratovna (Лучшие интеллектуальные исследования, 2023)
Annotation. This article details the use of didactic play methods in the classroom, which help students to develop professional knowledge, skills and abilities, intellectual development, and creative thinking.